CLINICAL, FUNCTIONAL AND RADIOLOGICAL ASSESSMENT OF RESULTS OF TOTAL KNEE REPLACEMENT: A MID-TERM FOLLOW–UP - DR. ANIL KUMAR. S. V; DR. VINEETHA VITTAL; DR. SAMARTH ARYA; DR. A. DEVADOSS (International Journal of Pharma and Bio Sciences, 2015)
A retrospective study was conducted to evaluate the results of 59 knee replacements done in 38 patients. Thirty patients replaced with 48 knees were available for the follow-up. The average period of the follow up was 4.5 years. There were 12 males and 18 females with average age of 56.83 years. The diagnosis was osteoarthritis in 21 patients, and rheumatoid arthritis in 9 patients. Eighteen patients underwent bilateral knee replacements (3 RA and 15 OA patients) and 12 patients had unilateral replacement (6 RA, 6 OA).Three types of prostheses were used: Total condylar prosthesis (25 knees), Post and cam type (9 knees), Ultra-congruent deep dish type (14 knees). Type of prosthesis were selected randomly and according to financial status of the patient. Clinical and Functional assessment was done by the knee Society Score (KSS) and Radiological assessment was by Knee Society Total Knee Arthroplasty Roentgenographic Evaluation and Scoring System. We concluded that most of our patients were replaced with Total Condylar Prosthesis knees and some of them had anterior knee pain. This was main reason for low KSS score with Total Condylar Prosthesis knees compared to Ultra-congruent polyethylene and Post and Cam. Even though knees replaced with Ultra-congruent polyethylene and Post and Cam had better KSS clinical and functional scores compared to Total Condylar Prosthesis, it was not statistically significant. Our 87.5% good to excellent results are on par with the other global studies.